Differences water harness and longevity rates in the peninsula of nicoya of Guanacaste and the otrher districts - Mora-Alvarado, Darner A. (2015)
Objective: to analyse drinking-water hardness characteristics and the longevity rates/10.000 inhabitants of the districts within the Nicoya Peninsula (‘Blue Zone’) and the rest of Guanacaste. The aim is to determine whether mineral content of water is a protective factor for quality and long life. Methodology: six steps were followed in order to meet the objective of the present study. First step was to perform at least 3.000 physical-chemical analysis of drinking-water, from 425 aqueducts of the 59 districts of Guanacaste. Secondly, total hardness (calcium carbonate + magnesium carbonate) was calculated using average values for each district. Third, using data from Censo 2011 longevity average rates/10.000 inhabitants were determined for three different age ranges: 80-89, 90-99, and >100 years old. Fourth step was to perform a frequency analysis, placing the longevity average rates throughout the total hardness ranges: 0-90, >90-180, >180- 270, and >270 mg/L. These data were used to analyse trends between total water hardness and longevity rates for each district. Fifth step consisted in the identification of the 29 districts of the ‘Blue Zone’, located within the Nicoya Peninsula. The total hardness values were compared to the longevity average rates/10.000 inhabitants values from the other 30 districts, used as control. Sixth step was to implement the ‘Student’s t-test’ for the differences between longevity within the three age ranges, in order to verify whether there was a statistically significant difference with 90% (p=<0,10), 95% (p=<0,05), and 99% (p=<0,01) confidence. Results Total drinking-water hardness averages show that 21 districts (35,6%) use ‘soft’ water, 23 (39%) ‘moderately hard’ water, 11 (18,6%) ‘hard’ water, and 4 (5,8%) ‘very hard’ water. Trend analysis between the four total hardness ranges and the longevity average rates, within the age rages of 80-89 and 90-99 years old, indicate there is a positive correlation between both factors along the 59 districts: the harder water is the higher longevity rate. On the other hand, water hardness averages appear to be markedly higher for the ‘Blue Zone’ than for the control districts throughout the three age ranges. However, the differences are statistically significant with 95% confidence in the first group (80-89 years old) and 90% in the second one (90-99 years old). Conclusions The results show there is a positive correlation between the consumption of ‘hard’ water and the longevity rates within people >80 years old. Drinking mineralised water for long periods of time is a protective factor for longevity and quality of life. Recommendations To verify if consumption of ‘hard’ water is a common protective factor for longevity within the remaining ‘Blue Zone’ throughout the world, i.e. Sardinia (Italy), Okinawa (Japan), Loma Linda (California, USA), and Icaria (Greece).